Simultaneous Effect of Aerobic Training and Resveratrol Supplementation on Interleukin-6 Serum Levels in Women With Type 2 Diabetes - Ensiyeh Yazdkhasti; Farnaz Seifi-SkiShahr; Mohammad Ebrahim Bahram (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims Diabetes pathogenesis is driven by a complex network of pro-inflammatory cells and cytokines, of which interleukin-6 (IL-6) plays a key role in the chronic inflammation associated with type 2 diabetes. The use of supplements and plant extracts and exercise to treat type 2 diabetes is common today. The aim of this study was to evaluate the simultaneous effect of aerobic training and resveratrol supplementation on IL-6serum levels in women with type 2 diabetes. Methods This study was a quasi-experimental study with a pre-test-post-test design and a control group, in which 24 women with type 2 diabetes were randomly assigned to three equal groups of supplement (age 55.25±5.11 years), training+supplement (400 mg resveratrol) (age 54.62±7.22 years), and control (age 52.25±8.60 years). The subjects practiced for six weeks and every week for three days for 40-60 min and at a heart rate of 45-65. Data analysis was performed using analysis of covariance and correlated t-test at the significant level of <0.05. Results The results showed that after the intervention, IL-6 serum levels in the aerobic training + supplement group (P=0.01) had a significant decrease compared to the supplement and control groups. Examination of intergroup changes shows that there was a significant difference in IL-6 levels between the training + supplement group and the supplement group (P=0.002, f=1.56). Also, the results of the Tukey post hoc test showed that there was a significant difference between the control group and the training + supplement group (P=0.003) and between the supplement group and the training+supplement group in IL-6 levels (P=0.031). Conclusion Based on the findings of the present study, it seems that concomitant use of resveratrol supplementation and aerobic training can reduce the levels of IL-6 and the supplement have anti-inflammatory and protective effects in women with type 2 diabetes.